Evaluation of Ultrasound Therapeutic Effect on Patients with Carpal Tunnel Syndrome Attending in a Tertiary Care Hospital of Bangladesh (BIRDEM Medical Journal, 2019)
Background: Carpal tunnel syndrome is a common condition in medical practice. Ultrasound therapy is a common non-surgical treatment of carpal tunnel syndrome including other modalities like the use of antiinflammatory agents and exercise. This study was designed to evaluate the effect of ultrasound therapy for the relief of symptoms of patients with carpal tunnel syndrome.Methods: This was a randomized controlled trial. This study as conducted in Department of Physical Medicine and Rehabilitation of Bangabandhu Sheikh Mujib Medical University, Dhakaduring the period from March 2014 to August 2014to evaluate the effect of ultrasound therapy on patients of carpal tunnel syndrome. Total 110 subjects were participated in this study and they were selected randomly. The patients were divided in two groups by lottery. For group A patients treatment schedule (Ultrasound therapy+ Exercise+ Wrist splint +NSAIDs) and group B (Exercise+ Wrist splint+ NSAIDs) were applied for a period of 6 weeks. Group A were compared to group B byVisual Analog Scale after 3weeks and 6weeks of treatment.Statistical analysis of the finding was done with the help of statistical package for social science version (SPSS) 19. The student t test used to analyze the level of significance, p< 0.05.Results: This study showed mean visual analogue scale (VAS) at pretreatment (W0) in group-A was 6.42 ±1.23 and in group-B was 6.17±0.74. Group-A was 1.82±0.43 and in group-B was 3.1±0.23 in their follow up after 3 weeks (W 3). Mean Visual Analogue scale in groupA- was 1.71(±0.52) and in group-B was 2.52(±0.49) at 2nd follow up (W 6) after 6 weeks . So these result reveled that group-A is significantly better than group-B.Conclusion: This study revealed that continuous mode of US therapy with exercise, wrist splint, NSAIDs have better outcome in case of Carpal tunnel syndrome patients.Birdem Med J 2019; 9(1): 70-73